An Analysis Of Break Even Point (BEP) In Profit Planning At Kerupuk Sri Rasa Factory In Bengkulu - Atika Indah Putri; Karona Cahya Susena; Suswati Nasution (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This study aims to analyze and find out the application of the Break Even Point in profit planning at Kerupuk Sri Rasa Factory in Bengkulu. The data analysis method used in this study is a quantitative descriptive method. The data were analyzed in the form of production reports, selling prices, sales volume and costs incurred in production. The results showed that in June, the Break Even point (BEP) was on the sales volume of 2,203 bales of Jalin crackers or Rp.22,025,939, and a margin of safety of 72.66%. In July, the results of the analysis calculation obtained the break-even point (BEP) on the sales volume of 2,060 bales of Jalin crackers or Rp.20,602,384. In August, the break-even point (BEP) was on the sales volume of 1,990 bales of Jalin crackers or IDR 19,898,990. In September the break-even point (BEP) was at sales volume of 1,950 bales of Jalin crackers or Rp.19,489,513. In October the break even point (BEP) was on sales volume of 2,073 bales of Jalin crackers or IDR 20,723,753. If the sales level is below the BEP point then the business will experience a loss and vice versa if it is above the BEP point then the business will make a profit. In profit planning, if in November you want to increase profits by 20%, then the calculation of sales that must be achieved from the previous month, namely, 20% from June, can increase sales by 9,046 bales of crackers or Rp. 90456172. From the results of the analysis that has been carried out that the break even point (BEP) method is suitable as a tool in profit planning at Kerupuk Sri Rasa factory in Bengkulu in order to find out at sales how much the breakeven point occurs, using this method it is possible to find out and determine production costs as a whole. maximum to avoid losses.